(untitled) (Palíndromo, 2018)
This article intends to investigate, through the work Arte Cemiterial, from artist Paulo Bruscky, the relationship between art and public sphere. Thus, I analyze the sociological concept of artistic agency to understand how this work acts both in the urban space, which was carried out, as in the public sphere that participates (the political field and the field of art to which it belongs). Chantal Mouffe’s theory of radical democracy and agonists artistic practices will be used here to compose this notion of artistic agency.